2021
DOI: 10.3390/cancers13235929
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Checkpoint Inhibition in the Treatment of Gastro-Esophageal Cancer: A Closer Look at the Emerging Evidence

Abstract: To date, several trials have evaluated the safety and efficacy of immune-checkpoint inhibitors (ICI) for the treatment of gastroesophageal cancers (GEC). In the US, ICIs have established indications for second-line treatment of microsatellite unstable tumors, while their use in third-line settings was recently withdrawn. Notably, the use of ICIs for first-line therapy of GEC is rapidly evolving, which currently includes high PD-L1 expressing tumors, irrespective of HER2 status, and in the adjuvant setting afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…At present, the most commonly used methods for preoperative staging of esophageal cancer mainly include computed tomography (CT), endoscopic ultrasonography (EUS) and positron emission tomography (PET) (16)(17)(18)(19)(20)(21). Among them, CT, especially enhanced CT, is the most commonly used examination method to exclude distant metastasis of esophageal cancer patients, which can accurately find the most common liver, brain and lung metastasis (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…At present, the most commonly used methods for preoperative staging of esophageal cancer mainly include computed tomography (CT), endoscopic ultrasonography (EUS) and positron emission tomography (PET) (16)(17)(18)(19)(20)(21). Among them, CT, especially enhanced CT, is the most commonly used examination method to exclude distant metastasis of esophageal cancer patients, which can accurately find the most common liver, brain and lung metastasis (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, exposure–efficacy simulations for patients with gastric cancer receiving the T‐DXd 6.4‐mg/kg dose suggested a similar incidence of ORR in Western patients and patients from Japan with gastric cancer, and a numerically lower rate of confirmed ORR in Western patients compared with patients from Japan. These results are potentially attributable to lower use of checkpoint inhibitors, which are approved for third‐line therapy for gastric cancer in some Asian countries, including Japan, but not in the United States, 26 and a higher proportion of patients having HER2 IHC 2+ status in the Western population. Exposure–safety simulations for patients with gastric cancer receiving the T‐DXd 6.4‐mg/kg dose suggested a lower rate of any‐grade ILD in Western patients than in patients from Japan, but comparable grade 3 or greater ILD rates, and a lower incidence of grade 3 or greater neutropenia and grade 3 or greater thrombocytopenia and a higher incidence of serious adverse events in Western patients than in patients from Japan.…”
Section: Discussionmentioning
confidence: 97%
“…Immunotherapy has evolved as a promising new treatment modality across cancer types ( 33 ). An available study ( 34 ) indicates that immune check-point inhibitors (ICIs) such as pembrolizumab and nivolumab can be used as a first-line treatment for patients with locally advanced EC. In 2020, Kojima et al ( 35 ) randomized 628 patients with advanced EC to pembrolizumab or chemotherapy.…”
Section: Definition and Progress Of Neoadjuvant Therapy For Esophagea...mentioning
confidence: 99%
“…Patients were identified in a phase 3 trial, with a positive score ≥10 had significantly higher 12-month OS with pembrolizumab versus chemotherapy (43% vs. 20%) and significantly lower rates of adverse events with treatment (18.2% vs. 40.9%). In 2019, a multicenter phase III trial ( 34 ) involving 419 patients randomized to nivolumab or chemotherapy showed a median follow-up for OS of 10.5 months in the nivolumab group and 8.0 months in the chemotherapy group. At a minimum follow-up of 17.6 months, OS was significantly improved with nivolumab versus chemotherapy (10.9 vs. 8.4 months, P=0.019).…”
Section: Definition and Progress Of Neoadjuvant Therapy For Esophagea...mentioning
confidence: 99%